Dedifferentiated gastrointestinal stromal tumour with features mimicking malignant PEComa/alveolar soft part sarcoma: An unusual type of morphological transformation following imatinib treatment - Kankanamage Malinda Amesh Karasinghe; Kesavan Sittampalam (Elsevier, 2021)
Gastrointestinal stromal tumours (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract. Dedifferentiation is a rare phenomenon in GISTs, most often following long-term Imatinib therapy and less frequently in de-novo fashion. According to the literature, the process of dedifferentiation is likely associated with genetic instability, rather than a result of acquisition of novel mutations in the common driver oncogenes. However, the exact underlying molecular basis of dedifferentiation is not well-established. Dedifferentiated GISTs show anaplastic features with loss of immunoreactivity for CD117 and DOG1. In this report, we present a rare and unique case of dedifferentiated metastatic GIST with a very unusual malignant PEComa/alveolar soft part sarcoma-like morphology. The molecular findings of our case also support the concept that dedifferentiation of GIST is independent of acquisition of additional novel mutations in the common driver oncogenes.